Cervical spine thrust and non-thrust mobilization for the management of recalcitrant C6 paresthesias associated with a cervical radiculopathy: a case report. - Hagan, Christopher R.; Anderson, Alexandra R. (Physiotherapy Theory & Practice, 2022)
The conservative management of cervical radiculopathy is supported by moderate evidence to include interventions such as manual therapy, traction, and therapeutic exercise. There is sparse evidence, however, to support specific manual therapy techniques, particularly thrust manipulation. A 35-year-old male presented to physical therapy with a clinical diagnosis of cervical radiculopathy. He complained of neck and upper arm pain with 1st and 2nd digit paresthesias. He was initially managed with repeated movements that restored the cervical range of motion and centralized neck and upper arm pain. Non-thrust upslope joint mobilizations resulted in improved sensation detection in the hand, but the paresthesias did not completely resolve. Immediately following cervical spine upslope thrust manipulation, symptoms fully resolved. Outcomes: The patient fully returned to prior level of function. His DASH score reduced from 40/100 to 2/100, PSFS improved from 1.66/10 to 9.66/10, and he reported to be 'a great deal better' on the GROC. This case demonstrates the safe and effective utilization of cervical spine thrust manipulation and non-thrust mobilization in the management of a patient with cervical radiculopathy with lingering paresthesias in the distal upper extremity.